2011
DOI: 10.1016/j.cognition.2011.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Male more than female infants imitate propulsive motion

Abstract: Few experimental studies investigate the mechanisms by which young children develop sextyped activity preferences. Gender self-labeling followed by selective imitation of same-sex models currently is considered a primary socialization mechanism. Research with prenatally androgenized girls and non-human primates also suggests an innate male preference for activities that involve propulsive movement. Here we show that before children can label themselves by gender, 6-to 9-month-old male infants are more likely t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 26 publications
0
17
0
1
Order By: Relevance
“…Thus, the gender effect is not specific to helping situations. It is possible that boys enjoyed pushing the lever more than girls similar to 6‐ and 9‐month‐old boys imitating propulsive actions more than girls (Benenson, Tennyson, & Wrangham, ; see Alexander & Wilcox, ; Christov‐Moore et al., ; for a more general review of gender effects). In a similar vein, the current results were obtained in a Western population of toddlers.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the gender effect is not specific to helping situations. It is possible that boys enjoyed pushing the lever more than girls similar to 6‐ and 9‐month‐old boys imitating propulsive actions more than girls (Benenson, Tennyson, & Wrangham, ; see Alexander & Wilcox, ; Christov‐Moore et al., ; for a more general review of gender effects). In a similar vein, the current results were obtained in a Western population of toddlers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, infant girls showed advantage over infant boys in fine motor skills (Touwen, ) and a meta‐analysis of 46 infancy studies, using a range of assessment procedures, showed higher levels of motor activity in boys than in girls (Campbell & Eaton, ). In addition, an experimental study found that, between the ages of 6 and 9 months, boys were more likely than girls to imitate propulsive movement (Benenson, Tennyson, & Wrangham, ).…”
Section: Sex Differences In Infants' Preferences and Abilitiesmentioning
confidence: 99%
“…Finally, sex differences have been reported in several other domains, including habituation behaviors (Creighton, 1984;Tighe & Powlison, 1978), perception of pictorial cues (Kavšek, 2003(Kavšek, , 2004, categorization (Arterberry & Bornstein, 2002), imitation of propulsive motion (Benenson, Tennyson, & Wrangham, 2011), perception of number (Moore & Cocas, 2006;Strauss & Curtis, 1981), and components of linguistic processing (Friederici et al, 2008;Lany & Gomez, 2008;Shucard, Shucard, & Thomas, 1987). However, many of these results are difficult to interpret, have not been replicated, and/or have inconsistent outcomes across studies.…”
Section: Cognitive Behaviormentioning
confidence: 99%